Sri Suparsih WANGSALAN SEBAGAI BAHAN DAN ALAT PENDUKUNG SAJIAN GENDHING - Sri Suparsih (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
This research is based on the writer’s interest in the application of wangsalan texts (cakepan), which are anelement of sindhenan, in a way that is appropriate (trep) to the performance of a gendhing. The appropriate(trep) application of wangsalan texts (cakepan) will support a better performance of the gendhing. The reasonfor this is that it was found, after a detailed study, that wangsalan and gendhing can be synchronized byapplying wangsalan texts (cakepan) in the correct and appropriate (trep) way. The method used for this researchis qualitative and the steps included a library study and observation. The library study was carried outby reading books and listening to cassettes. The observation included watching live performances of karawitanand also direct involvement in a number of performances. Several categories of wangsalan texts (cakepan) insindhenan were found that could be matched with particular gendhing. These were wangsalan that were concernedwith names of flowers, plants, the solar system, and natural phenomena (water, wind, fire, stone, etc.).These wangsalan texts (cakepan) in the sindhenan were applied to gendhing by matching the title and character(rasa) of the gendhing performed. It can be concluded, therefore, that there is a need for specific classificationof wangsalan texts (cakepan) to facilitate the application of these texts in the performance of gendhing.The researcher collected the wangsalan texts (cakepan) studied in this research from various oral and writtensources, and classified them according to the criteria determined by the researcher. Subsequently, thesetexts were matched or applied to gendhing in accordance with the title or character (rasa) of the gendhing.